Efficacy and tolerability of Roystonea regia lipid extract (D-004) and terazosin in men with symptomatic benign prostatic hyperplasia: a 6-month study. (June 2019) - Guzmán, Raúl; Fernández, Julio C.; Pedroso, Manuel; Fernández, Lilia; Illnait, José; Mendoza, Sarahí; Quiala, Ana T.; Rodríguez, Zunilda; Mena, Jilma; Rodíguez, Aylim; Campos, Marbelis; Sánchez, Carlos; et al.
Background: Benign prostatic hyperplasia (BPH), a common urological disease in aging men, frequently produces lower urinary tract symptoms (LUTS). Clinical studies have shown that terazosin relaxes the smooth muscle of the prostate and bladder, facilitates bladder emptying, improves LUTS, increases maximum urinary flow, and reduces the residual volume of urine. D-004, a lipid extract of the fruit of the Cuban royal palm ( Roystonea regia ), presents a similar efficacy to Saw palmetto. Clinical studies have demonstrated its efficacy and safety in short- and medium-term trials in patients with BPH. The objective of this study was to compare the efficacy and tolerability of D-004 with terazosin for 6 months on LUTS in patients with BPH. Methods: The present phase III study had an open, randomized, comparative design, with two parallel groups who received D-004 (320 mg/day) or terazosin (5 mg/day) for 6 months. The study included men at least 50 years of age, with evidence of the LUTS of moderate intensity according to the International Symptoms of the Prostate (IPSS). The effects on the IPSS Scale was the primary efficacy variable. The effects on the size of the prostate and the residual volume were secondary variables. The subjective self-perception of symptom relief at trial completion was a collateral outcome. Analysis was done by intention-to-treat. Results: The study included 100 men with a diagnosis of BPH, confirmed by digital rectal examination and ultrasonography, and moderate LUTS (IPSS score >7, <19). Baseline characteristics were similar in both groups. Nine patients did not continue the study: one from group D-004 (due to protocol violation) and eight from the terazosin group (six due to adverse events and two due to protocol violation; p < 0.01). D-004 and terazosin significantly reduced the IPSS scores at the end of the 6 months of therapy by 74.2% and 66.1%, respectively, with respect to baseline values. Comparisons between groups performed showed that, at the end of the treatment, D-004 was more effective ( p < 0.05) than terazosin in reducing the IPSS score. Although the average size of the prostate was reduced in both groups, this reduction reached statistical significance only for D-004. On the other hand, postvoid residual volume was significantly and similarly reduced in both groups. Both treatments were safe, while D-004 was better tolerated than terazosin. Conclusions: D-004 administered at a dose of 320 mg/day for 6 months showed comparable efficacy with terazosin (5 mg/day) in reducing the LUTS (IPSS score), producing a significant decrease in prostate volume and postvoid residual volume. Both treatments were safe, with better tolerability for D-004 as compared with terazosin.